RECONCEPTUALIZING CLASSROOM IMMERSION IN ARABIC AS A FOREIGN LANGUAGE: A PEDAGOGICALLY ENGINEERED MODEL IN A NON-RESIDENTIAL CONTEXT - Mochammad Indra Yumanto; Ibnu Mas'ud Luthfi; Kamal Yusuf; Nasaruddin; Muflihah; Hasyim Asyari (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
Language immersion has traditionally been associated with native-speaker environments or residential systems, a view that has limited the pedagogical imagination of Arabic as a Foreign Language (AFL) instruction in non-residential contexts. Addressing this gap, the present study reconceptualizes classroom immersion as a pedagogically constructed, classroom-centered model. Using a qualitative case study design at Madrasatul Alsun in Sidoarjo, the study draws on interviews with institutional leaders, teachers, and students, classroom observation, document analysis, and field notes. The findings show that classroom immersion is constructed through the integration of Arabic as the primary medium of instruction, the staged organization of comprehensible input, interactional design, the prioritization of acquisition over explicit learning, and the extension of language exposure through institutionally supported semi-immersive practices. The study concludes that this model does not constitute full or natural immersion; rather, it is best understood as a pedagogically designed semi-classroom immersion model that can be built, sustained, and adapted in non-residential contexts beyond reliance on a pre-existing natural language environment.